Systematic review of the performance and clinical utility of point of care HIV-1 RNA testing for diagnosis and care. - Clara A Agutu (PLoS ONE, 2019)
Background Point of-care (POC) HIV-1 RNA tests which are accurate and easy to use with limited infrastructure are needed in resource-limited settings (RLS). We systematically reviewed evidence of POC test performance compared to laboratory-based HIV-1 RNA assays and the potential utility of these tests for diagnosis and care in RLS. Methods Studies published up to July 2018 were identified by a search of PUBMED, EMBASE, Web of Science, CINAHL and Cochrane Central Register of Controlled Trials. Studies evaluating the use of POC HIV-1 RNA testing for early infant diagnosis (EID), acute HIV infection (AHI) diagnosis, or viral load monitoring (VL), compared to centralized testing, were included. Separate search strategies were used for each testing objective. Results 197 abstracts were screened and 34 full-text articles were assessed, of which 32 met inclusion criteria. Thirty studies evaluated performance and diagnostic accuracy of POC tests compared to standard reference tests. Two of the thirty and two additional studies with no comparative testing reported on clinical utility of POC results. Five different POC tests (Cepheid GeneXpert HIV-1 Quantitative and Qualitative assays, Alere q HIV-1/2 Detect, SAMBA, Liat HIV Quant and Aptima HIV-1 Quant) were used in 21 studies of VL, 11 of EID and 2 of AHI. POC tests were easy to use, had rapid turnaround times, and comparable accuracy and precision to reference technologies. Sensitivity and specificity were high for EID and AHI but lower for VL. For VL, lower sensitivity was reported for whole blood and dried blood spots compared to plasma samples. Reported error rates for Cepheid GeneXpert Qual (2.0%-5.0%), GeneXpert Quant (2.5%-17.0%) and Alere q HIV-1/2 Detect (3.1%-11.0%) were higher than in WHO prequalification reports. Most errors resolved with retesting; however, inadequate sample volumes often precluded repeat testing. Only two studies used POC results for clinical management, one for EID and another for VL. POC EID resulted in shorter time-to-result, rapid ART initiation, and better retention in care compared to centralised testing. Conclusions Performance of POC HIV-1 RNA tests is comparable to reference assays, and have potential to improve patient outcomes. Additional studies on implementation in limited-resources settings are needed.